Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Les outils de rappel ont été conçus à l’intention du personnel et du public, comme moyen de sensibilisation et de rappel de la signification et de l’importance de l’offre active. Grâce à ces outils, les patients et les membres de leur famille sont en mesure de comprendre qu’ils peuvent recevoir des services dans la langue officielle de leur choix au sein des organisations du Réseau de santé Horizon. Certains des outils servent également de ressources pour le personnel, les appuyant dans leur pratique de l’offre active. Ces outils ontété intégrés à une plateforme intranet virtuelle où les gestionnaires peuvent dorénavant trouver un ensemble de ressources, de politiques et de procédures concernant les langues officielles.

Co-development of a Web-based hub (eSocial-hub) to combat social isolation and loneliness in Francophone and Anglophone seniors in linguistic minority context (Quebec, Manitoba, and New Brunswick): Protocol for a mixed methods interventional study - Beogo, Irissa; Ramdé, Jean; Nguemeleu Tchouaket, Eric; Sia, Drissa; Bationo, Nenila Jean-Claude; Collin, Stéphanie; Anne, Abdoulaye; Gagnon, Marie-Pierre (JMIR Research Protocols, 2021)
Background: The first wave of the COVID-19 pandemic has severely hit Canadian nursing facilities (81% of deaths). To this toll, public health measures (eg, visitation restriction) have subsequently deepened the social isolation and loneliness of residents in nursing facilities (NFs), especially those in linguistic minority settings: Anglophone institutions in Quebec and Francophone institutions outside Quebec. However, very few COVID-19 initiatives targeting these populations specifically have been documented. Given the limited number of NFs serving linguistic minorities in Canadian populations, families and loved ones often live far from these facilities, sometimes even in other provinces. This context places the digital solutions as particularly relevant for the present COVID-19 pandemic as well as in the post–COVID-19 era. Objective: This project aims to co-develop a virtual community of practice through a web-based platform (eSocial-hub) to combat social isolation and loneliness among the older people in linguistic minority settings in Canada. Methods: An interventional study using a sequential mixed methods design will be conducted. Four purposely selected NFs will be included, 2 among facilities in Manitoba and 2 in New Brunswick; and 2 Anglophone NFs in Quebec will serve as knowledge users. The development of eSocial-hub will include an experimental 4-month phase involving the following end users: (1) older people (n=3 per NF), (2) families of the participating older people (n=3 per NF), and (3) frontline staff (nurse and health care aid; n=2 per NF). Results: Activities and solutions aiming at reducing social isolation and loneliness will be implemented and then evaluated with the project stakeholders, and the best practices generated. The assessment will be conducted using indicators derived from the 5 domains of the Consolidated Framework for Implementation Research. The project will be led by an interdisciplinary team and will involve a multisectoral partnership. Conclusions: The project will develop a promising and generalizable solution that uses virtual technology to help reduce social isolation and loneliness among the older people.

A test of French phonology: construction and use - Bérubé, Daniel; Bernhardt, B. May; Stemberger, Joseph P. (Canadian Journal of Speech-Language Pathology & Audiology, 2015)
Abstract: Clinicians have had limited resources for conducting phonological evaluations of Canadian Francophone children and, to this day, there are no standardized tests of French-Canadian phonology (Brosseau-Lapre, Rvachew, Arcand, & Leroux, 2011). Recently, preliminary normative data were collected with a French screening tool in Quebec, with results indicating that the screening tool is sensitive in identifying children with protracted phonological development (MacLeod, Sutton, Sylvestre, Thordardottir, & Trudeau, 2014). The current paper presents another new assessment tool for Canadian French phonology (developed for Manitoba French) to evaluate the segments and word structures of Canadian French phonology in depth within the context of a nonlinear phonological framework. The objectives of this article are: (a) to provide an overview of nonlinear phonology, and demonstrate how models of linear and nonlinear phonology account for non-adjacent segments, (b) to describe Manitoba French phonology, (c) to examine the phonological characteristics of the French word list (consonants, vowels, and word structures), and (d) to explain briefly how to administer, transcribe, and analyze data from the assessment tool. Abrégé: Les orthophonistes ont peu d'options pour l'evaluation phonologique du francais canadien chez les enfants et a ce jour il n'y a encore aucun test norme pour ce type d'evaluation (BrosseauLapre, Rvachew, Arcand, & Leroux, 2011). Recemment, une collecte de donnees preliminaires a ete effectuee aupres des enfants francophones au Quebec avec un outil francais de depistage de la phonologie et les resultats indiquent que l'outil est sensible pour identifier des enfants ayant des troubles de la phonologie (MacLeod, Sutton, Sylvestre, Thordardottir, &Trudeau, 2014). Ce rapport-ci presente un nouvel outil pour l'evaluation detaillee de la phonologie pour le francais canadien (elabore pour le francais du Manitoba), dont la structure vise a couvrir l'inventaire complet des phonemes et des structures de mots du francais canadien, dans le cadre theorique de la phonologie non lineaire. Les objectifs du rapport sont : (a) de presenter un survol de la phonologie non lineaire et demontrer comment les modeles de phonologie lineaire et non lineaire expliquent les phenomenes impliquant des segments non adjacents, (b) de decrire, brievement, la phonologie du francais Manitobain, (c) d'examiner les caracteristiques phonologiques de la liste de mots francais (les consonnes, les voyelles, et les structures du mot) et (d) d'expliquer brievement comment administrer, transcrire et analyser les donnees du test.

A comparison of two phonological screening tools for French-speaking children - Bérubé, Daniel; Macleod, Andrea A. N. (International Journal of Speech-Language Pathology, 2022)
Purpose: To examine two screening tools for phonological production, the Evaluation Sommaire de la Phonologie chez l’enfant d’âge préscolaire (ESPP) and the Test de Phonologie du Français Canadien-Dépistage (TPFC-D), developed according to differing theoretical perspectives. The TPFC-D, designed according to nonlinear phonology, includes more words and contains a greater variety of segments across word structure as compared to the ESPP, which was guided by a linear phonological framework. The greater response rate to test items, time of administration, and phonological complexity were expected on the TPFC-D. Method: Each screening tool was administered to 14 4-year-old French-speaking children living in Central Canada. Paired samples t-tests compared children’s responses on the two tasks with regards to (a) response rate and time of administration, (b) an overall percentage of consonants correct (PCC) and percentage of vowel correct (PVC), and (c) complexity of productions (i.e. PCC and PVC in relation to word structure, Word Shape Match, Whole Word Match, Phonological Mean Length of Utterance (pMLU) and Proportion of Whole-Word Proximity). Result: Item response rates were higher for the TPFC-D whereas time of administration, PCC and PVC were similar for both the ESPP and TPFC-D. Complexity measures showed a higher proportion of deletions in clusters and higher pMLUs on the TPFC-D compared to the ESPP. Conclusion: Both screening measures are appropriate for speech-language pathologists who want to assess quickly pre-school-aged children. Since the TPFC-D is phonologically more complex, it is recommended for clinicians needing to screen children who likely present with multiple speech sound errors across their phonological system.

GUIDELINES - Interpreting and companion serivces models to facilitate access to health services for Francophone and Acadian minoritycommunities (INTACC) - Bowen, sarah; Renée, Chartier; Richard, Lise (2016)
These guidelines were written as a guide for service providers to gain an understanding of the competencies, roles, responsibilities, and limits of interpretation and accompaniment services. They also lay out an Interpreters’ Code of Ethics. The document was prepared for the Société Santé en français’ INTACC

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Le recensement des outils de travail disponibles en français pour les professionnels oeuvrant dans le domaine de la santé : un rapport de la méthodologie utilisée par les physiothérapeutes - Casimiro, Lynn; Fortin, Murielle; Moisan, France; Tremblay, Louis E. (Reflets, 2002)

Une réalité qu’on ne peut ignorer : portrait régional des violences faites aux femmes des comtés de Prescott-Russell et les services communautaires disponibles pour les femmes et les familles. Récit d’une recherche-action - Coderre, Cécile (Reflets, 2016)

Active Offer - A culture of respect, a culture of excellence - Commissariat aux langues officielles (2017)

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)

L’offre active une culture de respect, une culture d’excellence : guide complet - Commissariat aux langues officielles (2017)

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

Les Petits et les Grands amis : Faciliter des échanges et développer des attitudes favorables entre les générations en milieu minoritaire. - de Moissac, Danielle; Arbez, Dominique; Alper, David; Bourrier, Patricia (Université de Saint-Boniface, 2021)
Dans la francophonie canadienne en contexte minoritaire, la population croissante d’aînés est à risque d’isolement social en raison des effets du vieillissement et du statut linguistique minoritaire. Les aînés vivant avec la démence sont davantage vulnérables à l’isolement, ce qui peut avoir comme conséquence d’aggraver le déclin cognitif et psychologique. D’autre part, la mobilité familiale, en particulier celle des familles immigrantes, fait en sorte que les échanges entre générations sont moins fréquents, tant pour les enfants que pour les aînés. Ce manque d’exposition et d’échanges entre les générations peut avoir un effet sur les enfants et mener à une perception défavorable des personnes âgées. Des études ont démontré que la participation aux programmes intergénérationnels favorise la santé physique et mentale des aînés, ainsi que leur engagement social. Pour les enfants, ces programmes favorisent leurs compétences sociales et émotionnelles et le développement d’attitudes positives à l’égard des aînés. Les programmes visant les aînés avec la démence et les enfants d’âge préscolaire suggèrent une attention particulière aux choix d’activités pour maintenir l’intérêt des deux groupes tout en respectant leurs capacités physiques et cognitives. Un programme intergénérationnel a été mis en place pour pallier l’isolement social des aînés et favoriser le développement d’attitudes positives chez les enfants à l’égard des aînés tout en reflétant la langue et les diverses cultures de la francophonie manitobaine. Une étude a été menée, ayant comme objectifs d’examiner l’impact de cette initiative sur le sentiment d’isolement social des résidents aînés d’un foyer de soins de longue durée et la perception des enfants quant aux aînés. Un programme intergénérationnel comprenant 8 séances d’activités a eu lieu à l’automne 20 9 au foyer de soins de longue durée dans un espace permettant aux enfants et aux aînés de participer à des activités de grand rassemblement et des activités en petits groupes. Les enfants du service de garde éducatif se déplaçaient une fois par semaine pour y participer. Des entrevues semidirigées ont été effectuées avant et après le programme intergénérationnel auprès ) des enfants, pour qualifier leur perception des personnes âgées et 2) auprès des aînés, en ce qui a trait à leur réseau social et leur sentiment d’isolement. De plus, les parents/ tuteurs des enfants participants ont été invités à compléter un questionnaire sur l’expérience de leur enfant auprès des personnes âgées avant les sessions intergénérationnelles. Les enfants participants ont pu créer des dessins commentés représentant leurs expériences avec les aînés à la suite de leur participation aux sessions intergénérationnelles. De plus, des observations ont été faites par des assistants de recherche lors des séances d’activité. Quelques membres du personnel du foyer de soins de longue durée et du service de garde éducatif ont également rempli un questionnaire d’évaluation de l’activité intergénérationnelle. Ainsi, l’ensemble des perspectives nous a permis de mieux saisir les effets des échanges intergénérationnels sur les participants.

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Mental health status and help-seeking strategies of international students in Canada - de Moissac, Danielle; Graham, Jan Marie; Prada, Kevin; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Canadian Journal of Higher Education, 2020)
International students are at heightened risk of developing psychological distress, yet little research has been conducted on their mental health or support needs. This quantitative study focused on undergraduate students at two mid-sized universities in Manitoba, Canada. Online and paper surveys were completed by 932 participants, of whom 21% identified as international students. This paper, descriptive in nature, outlines the sociodemographic profiles, current mental health status, psychological characteristics, and coping strategies of international students compared to domestic students in each institution. Data show that international students are more likely to report excellent mental health, score higher on the mental health scale, and report higher life satisfaction, higher self-esteem, and more positive body image than domestic respondents. However, they are less likely to talk about their hardships. Providing culturally-adapted supports that take into consideration ethnolinguistic differences, religious practice, and mental health literacy will better meet the needs of international students on campus.

Profil des ressources des communautés francophones en milieu minoritaire - Deroche, Francine; Simard, Anne; Di Ruggiero, Erica; Levesque, Johanne (Reflets, 2007)
Le Réseau canadien de la santé (RCS) est une initiative nationale financée par Santé Canada. Le Réseau favorise l’accès à une information fiable, crédible et continuellement mise à jour, sur la santé et vient renforcer les réseaux existants de promotion de la santé. Le RCS a mené une enquête pour identifier quelles sont les informations disponibles sur la santé dans les communautés francophones vivant en milieu minoritaire. Il s’agit là d’un point de départ pour permettre au RCS de planifier et de mettre en œuvre des services en français pertinents. Les objectifs de l’enquête étaient: • d’identifier et d’établir le profil des organismes qui traitent de la santé des Francophones; • d’identifier les types d’organismes recommandés comme sources d’information aux consommateurs et consommatrices et aux intermédiaires de la santé; • d’identifier les ressources existantes les plus souvent demandées par les consommateurs et consommatrices et les intermédiaires de la santé et, • d’identifier les lacunes en matière d’informations sur la santé des francophones

Démonstration de la valeur ajoutée de la collecte de l'identité linguistique [webinaire] - Desaulniers, Jacinthe; Manseau, Jasmin (Dans la série Découverte de Société Santé en français, 2017)

Des outils efficaces pour colliger des informations sur la capacité du système de santé à offrir des services en français: Démonstration en Ontario. [webinaire] - Desaulniers, Jacinthe; Pagé, Jean-Francois (2017)

Le démarrage d'un programme national de recherche sur la santé des communautés francophones minoritaires - une initiative du Consortium national de formation en santé - Desbiens, Francine (Reflets, 2005)

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Trousse d’outils sur les services en français French Language Services Toolkit - Dumont, Marthe; Doucet-Simard, Suzy (2013)

Visualisation des données sur l’offre et la demande de services en soins de longue durée en Ontario: un portrait régional de de l'offre et des besoins réalisé à l'aide de la plateforme dynamique Power-BI de Microsoft (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Visualization of data on the supply and demand for French-language long-term care services in Ontario: A regional snapshot of French-language long-term care supply and demand in Ontario,created using Microsoft's dynamic Power-BI platform (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Tableaux de bord : L’offre et la demande de services de santé en français - Soins de longue durée. (Power-BI, version bêta) - Duong, Patrick; Timony, Patrick E.; Glaude, Normand; Bouchard, Louise (Forces-Santé - Vitrine de données, 2026)
Résumé Ce tableau de bord propose une visualition interactive des données afin d'illustrer le potentiel de l'analyse géographique et de mieux compremdre les besoins des communautés francophones de l'Ontario en matière de soins de longue durée, dans une perspective d'équité et d'accès aux services. Abstract This dashboard provides an interactive visualization of data to illustrate the potential of geographic analysis and to better understand the long-term care needs of Ontario's Francophone communities, with a focus on equity and access to services.

L'offre active : la meilleure façon de prendre soin de notre santé - Emilie, O’Regan Martens; Roger, Gervais (2015)

Étude des services sociaux et de santé pour les personnes âgées francophones dans l'Est ontarien (RLISS de Champlain) - Fédération des aînés et retraités francophones de l'Ontario (FARFO) régionale d'Ottawa et GReFoPS (2019)

Guide de fonctionnement du système de santé à Terre-Neuve-et-Labrador - Fédération des francophones de Terre-Neuve et du Labrador (FFTNL) (2025)
Déménager dans un nouveau pays et tenter de s’intégrer dans sa nouvelle communauté peut être très stressant. Dans ce contexte, naviguer le système de santé peut représenter des défis particuliers pour les nouveaux arrivants qui choisissent de s’installer à Terre-Neuve-et-Labrador. L’objectif de ce guide est donc de faciliter la compréhension du système de santé de la province pour les nouveaux arrivants. il propose certaines ressources spécifiques pour les francophones.

Liminaire: Les enjeux reliés à la santé des communautés francophones en situation minoritaire - Forgues, Éric; Guignard Noël, Josée; Landry, Rodrigue (Francophonies d’Amérique, 2009)

A guide for Planning and Providing Francophone Long-term Care Services - Learning from Pavillon Omer Deslauriers (POD) at Bendale Acres and Other Franch Language Health Services for Seniors in Canada - FRENCH HEALTH NETWORK OF CENTRAL SOUTHWESTERN ONTARIO (2017)

Systematic Search and Evaluation of mobile Apps for Wound Care Available in French-Language in Canada - Gagnon, Julie; Chartrand, Julie; Probst, Sebastian; Maillet, Éric; Reynolds, Emily; Chaplain, Valérie; St-Jean, Heidi; East, Raphaelle; Lalonde, Michelle (Canadian Journal of Nursing Research, 2025)
Background Wounds are a significant national health concern, impacting individuals, healthcare systems, and the environment. Despite efforts by organizations to promote evidence-based practices, gaps persist between theory and nurse practice in wound care. Mobile apps show promises in enhancing wound care delivery, but their rapid evolution, including adaptations into different languages such as French, raises concerns about reliability and regulation. Evaluating these apps is crucial for ensuring patient safety and effective wound management. Purpose To review and assess mobile wound care apps available in French for healthcare providers in Canada. Methods A systematic search was conducted across the literature and the two main Canadian online app stores (App Store and Google Play). The included mobile apps underwent quality evaluation using the user version of the Mobile Application Rating Scale (uMARS). Results The initial search retrieved 1,550 apps, of which 260 were screened and 5 included. Included apps were from France and were available on both stores. These apps varied in features, including wound dressing directory (n= 3), best practices reminders (n = 2), photography management and digital wound tracking (n = 1), and total body surface area calculator (n= 1). Evaluation using uMARS indicated total averages range from 3.52/5 to 4.10/5. The results offer scant insight into the design and evaluation of the apps included. Conclusions The study highlights the need for development and validation of a French wound care app tailored to Canadian healthcare contexts and best practice recommendations, emphasizing collaboration among nurses and stakeholders in technology enhancement for the benefit of Canadians’ health.

Differences in experiences with episodic virtual care based on language of comfort for healthcare services in New Brunswick, Canada - Gallant, François; Forgues, Éric; Moffitt, Julie; Lavergne, M Ruth (BMC Primary Care, 2026)

En santé, on gagne à bien se comprendre (court) - Argumentaire pour des soins de santé de qualité en français; La traduction-interprétation et l’accompagnement comme solutions transitoires - Gauthier, Hubert (2016)

En santé, on gagne à bien se comprendre (long) - Argumentaire pour des soins de santé de qualité en français; La traduction-interprétation et l’accompagnement comme solutions transitoires - Gauthier, Hubert (2016)

Démonstration d’une méthodologie mettant à profit les modèles de Rasch : l’exemple d’une échelle de la mesure de l’offre active de services en français. - Grondin, Julie; Dionne, Éric; Savard, Jacinthe; Casimiro, Lynn (Regards actuels et prospectifs sur l’évaluation des apprentissages complexes en éducation dans le domaine de la santé, 2017)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Client and family information sheet: Access to health and social services in Official Languages Standard - Health Standards Organization (2018)
The CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages Standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. This information sheet explains what should be expected from health and social service organizations applying this standard.

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

Feuillet d'information pour les usagers et les familles : norme sur l'Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Ce feuillet d'information explique ce à quoi les usagers peuvent s'attendre des organismes de santé et de services sociaux qui appliquent cette norme.

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)
Le présent rapport a été conçu en tant que ressource pour aider l’"Équipe santé Enfants avant tout" à élaborer une stratégie de recrutement, de maintien en poste et de formation des ressources humaines dans la région sanitaire de Champlain, en Ontario. Le rapport a été préparé par l’Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (« l’Institut du savoir »). L’Institut du savoir crée des liens, transmet des connaissances et tire parti de son expertise pour améliorer les compétences des prestataires de services directs et des organismes de l’Ontario afin de renforcer les programmes et les services de santé mentale de l’Ontario pour tous les enfants, les jeunes, les familles et les prestataires de soins. Nous voulions savoir ce que font les organismes — particulièrement ceux du secteur de la santé — pour recruter des prestataires de services qui maîtrisent le français. Nous voulions aussi nous renseigner sur les pratiques de recrutement fondées sur des données probantes décrites dans la littérature. Les stratégies et les principes directeurs présentés dans cette ressource sont tirés d’une analyse contextuelle qui comprenait un examen rapide et non systématique de la littérature. De plus, nous avons consulté des intervenant.e.s clés et des leaders dans le domaine qui ont une expérience directe de recrutement de prestataires de services qui maîtrisent le français.

Canadian French Translation and Preliminary Validation of the Conformity to Masculine Norms Inventory: A Pilot Study - Jbilou, Jalila; Levesque, Natasha; Sonier, René-Pierre; Tully, Phillip J.; Pinette-Drapeau, Iza; Sonier, Véronique; Charbonneau, Andréanne; Greenman, Paul S.; Grenier, Jean; Chomienne, Marie-Hélène (American Journal of Men's Health, 2021)
Conformity to masculine norms has been linked to poor mental and physical health outcomes. Its valid assessment among subgroups of the population is therefore a crucial step in the investigation of intercultural variability in the enactment of masculinity, as well as its causes, costs, and benefits. The present pilot study aimed to adapt and conduct a preliminary validation of a French version of the Conformity to Masculine Norms Inventory (CMNI-22), a self-report questionnaire designed to assess overall conformity to male gender standards. The French adaptation of the CMNI-22 (CanFr-CMNI-22) was developed using a forward-backward translation process. The data from a sample of 57 Canadian French men (23–81 years old), collected at two time points 2 weeks apart, were then analyzed to investigate the psychometric properties and factor structure of the CanFr-CMNI-22. Findings indicated adequate internal reliability of the global scores and highly satisfactory test–retest reliability. Correlations with the Male Role Norms Inventory-Short Form (MRNI-SF) at both time points also showed strong convergent validity. Overall, the CanFr-CMNI-22 appears to be a reliable and valid instrument to assess conformity to traditional masculine gender norms in French-speaking men from the general population. This study is a key step in a research process aiming to validate the Canadian French version of the CMNI and contributes to enhance inclusive research and clinical care to foster men’s health.

Les bienfaits de la socialisation au programme de jour du Centre de services Guigues (CSG) sur la santé des personnes âges francophones ayant vécu l'isolement ou la solitude dans la région d'Ottawa - Kajuka, Dale (Université Laurentienne, 2017)

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

Le programme de télésanté de prévention des chutes Marche vers le Futur : développement et retombées d’une communauté de pratique franco-canadienne - O’Neil, Jennifer; Dionne, Nathalie; Cardinal, Dominique; Savard, Jacinthe (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
Résumé Le programme de télésanté Marche Vers le Futur (MVF) a eu un impact positif sur le bien-être des personnes âgées francophones et sur leur accès aux services de prévention des chutes au Canada. L’objectif de ce projet était de développer et de mettre en place une communauté de pratique (CdP) facilitant le partenariat et le partage des connaissances entre les animateurs du programme MVF. La création de cette CdP a permis à vingt-deux animateurs de cinq provinces de partager des stratégies de recrutement, de promotion du programme et de sensibilisation quant aux besoins des personnes âgées francophones au pays. Quatre rencontres virtuelles ont permis d’identifier les obstacles à la pérennité de MFV, les facteurs facilitant la mobilisation des connaissances ainsi que les initiatives de formation continue. La CdP a permis de renforcer les réseaux de partenariat entre les chercheurs et les animateurs du programme MVF, ce qui pourrait avoir un impact important sur l’équité en santé chez les personnes âgées francophones vivant en situation minoritaire au Canada. Abstract Marche vers le Futur (MVF) is a telehealth program that has demonstrated a positive impact on the access to fall prevention services in Canada and the wellness of older Francophone adults living in minority situations. This project aimed to develop and implement a community of practice (CoP) to facilitate partnership and knowledge-sharing between MVF program facilitators across francophone communities in Canada. The creation of this CoP enabled twenty-two facilitators from five provinces to share strategies for recruiting, promoting, and sustaining the program as well as continuing to raise awareness around the importance of health prevention services tailored for older Francophone adults in Canada. Four virtual meetings were held to identify sustainability barriers, knowledge mobilisation facilitators, and continuing education initiatives. The CoP allowed to strengthen the partnership between researchers and program facilitators across diverse provinces which could impact health equity among older Francophone adults living in minority communities in Canada.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

HR Support Kit – Pathway to Bilingual services - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Trousse d’appui RH – Vers un service bilingue - Regroupement des intervenantes et intervenants francophones en santé et en services sociaux de l'Ontario (2012)

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Les services en français, un facteur de qualité -Argumentaire et cadre d’analyse d’impact à l’attention des Réseaux locaux d’intégration des services de santé (RLISS) et des fournisseurs de services de santé (FSS) de l’Est et du Sud-Est de l’Ontario - Réseau des services de santé en français de l’Est de l’Ontario (2012)
Le document Les services en français, un facteur de qualité des services de santé élaboré par le Réseau des services de santé en français de l’Est de l’Ontario (le Réseau) a pour objectif de : - sensibiliser et informer des impacts de la barrière linguistique sur la qualité des services de santé en français et donc sur l’amélioration de l’état de santé de la population francophone; -véhiculer l’importance d’une planification de projets et d’initiatives en santé qui tiennent compte des barrières linguistiques afin d’améliorer l’état de santé de la communauté francophone vivant en contexte minoritaire. Pour ce faire, le Réseau a développé un argumentaire et un cadre d’analyse d’impact de la barrière linguistique, ayant pour appellation la lentille francophone, à l’attention des réseaux locaux d’intégration des services de santé (RLISS) et des fournisseurs de services de santé (FSS) des régions de Champlain et du Sud-Est.

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Carte interactive- Le Nouveau-Brunswick - Réseau en immigration francophone du Nouveau-Brunswick (2022)
Ce site présente une carte interactive qui permet de rechercher différents services, dont les services de santé, disponibles en français au Nouveau-Brunswick

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Implementing the Optimal Model of Long-Term Care for Francophones and Other Cultural and Linguistic Minority Groups - Réseau franco-santé du Sud de l'Ontario and partners (2019)

Concrétiser le modèle de soins de longue durée à l’intention des francophones et d'autres membres de groupes culturels et linguistiques minoritaires - Réseau franco-santé du Sud de l’Ontario et partenaires (2020)

Guide santé pour les nouveaux arrivants en Nouvelle-Écosse - Réseau santé en Nouvelle-Écosse, Immigration francophone Nouvelle-Écosse et Réseau en immigration francophone de la Nouvelle-Écosse (2022)

Guide santé pour les nouveaux arrivants aux territoires du Nord-Ouest - Réseau TNO Santé (2022)

Passeport santé pour les nouveaux arrivants aux Territoires du Nord-Ouest - Réseau TNO Santé (2022)

Trousse d’accompagnement pour l’examen médical du nouvel arrivant - Sanou, Baroma; Gauthier, Alain; Chomienne, Marie-Hélène; Prud'homme, D.; Kpazaï, G. (2018)

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Working together to implement the Active offer of French-language Services - Particpants's guide - Santé en français (2016)

Guide de navigation du réseau de la santé et des services sociaux du Manitoba - Santé en français Manitoba (2024)
L’élaboration du présent guide visait à faciliter le cheminement des gens dans le réseau manitobain de la santé. Il se veut un outil pratique permettant aux personnes francophones de s’orienter rapidement dans le réseau de la santé. Les nouveaux arrivants, les voyageurs ou les résidents de longue date aux prises avec un nouveau problème de santé ont souvent beaucoup de questions à poser et un grand besoin d’aide pour trouver les bonnes ressources dans le réseau. Compte tenu de sa mission d’améliorer l’accès à des services de santé et des services sociaux d’excellente qualité en français, Santé en français a collaboré avec le Réseau en immigration francophone (RIF) du Manitoba pour élaborer le présent guide avec en tête les objectifs suivants : • Aider les gens à comprendre le réseau manitobain de la santé. • Faire connaître les principales coordonnées et les voies d’accès, et renseigner sur la façon d’accéder aux services publics et à certains services privés.

Savoir penser, agir et rêver : pour la santé en français au Manitoba - Santé en français (Manitoba) (2015)

Balises-Modèles de services d'interprétariat et d'accompagnement pour faciliter l'accès aux services de santé des communautés francophones et acadiennes vivant en situation minoritaire (INTACC) - sarah, Bowen; Richard, Lise; Chartier, renée (2016)
Ces balises ont été développés afin de guider les pourvoyeurs de services avec la compréhension des compétences, rôles, responsabilités et limites des services d’interprétariat et d’accompagnement, et étale les Principes éthiques de l’interprète. Ce document fut préparé dans le cadre du projet INTACC de la Société Santé en français par Dr Sarah Bowen, Renée

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Évaluation métrologique de la Mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Benoît, Josée; Bouchard, Pier (Reflets, 2014)
Comment peut-on mesurer l’impact des actions entreprises pour améliorer l’offre active de services sociaux et de santé en français dans les communautés francophones en situation minoritaire? Un questionnaire mesurant premièrement les comportements individuels de l’offre active et deuxièmement la perception du soutien organisationnel à faire de l’offre active a été créé. La validité de contenu de la Mesure de l’offre active de services en françaisen contexte minoritaire a été établie à l’aide d’une recension d’écrits, de consultations menées auprès d’expertes et d’experts et d’un sondage Delphi pancanadien. Sa fidélité a été examinée à partir de données recueillies auprès de récents diplômés en santé et en service social. L’outil démontre une bonne consistance interne et des études auprès d’un plus large échantillon sont nécessaires pour augmenter la confiance envers sa stabilité temporelle. Il s’agit des premiers pas d’une démarche visant à mesurer l’évolution des comportements d’offre active à la suite d’activités de formation ou de changements organisationnels en faveur de services en français. Une telle mesure est aussi susceptible d’être utile dans les recherches visant à saisir les déterminants de ces comportements d’offre active. Mots-clés : Offre active de services en français, formation des professionnelles ou professionnels en santé et services sociaux, soutien organisationnel, évaluation, minorité, langue et services, qualité des soins et services, sécurité des clientes ou clients/patientes ou patients

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, we present the behaviours we have identified encouraging and demonstrating the active offer (AO) of social services and health care in French in minority settings, how we measured them, and how we used these measurements to identify the determinants of AO. We will discuss the tools we developed to measure individual AO behaviours, individual perception of organizational support for AO, and personal characteristics that influence AO behaviours (determinants). Various quantitative methods were used to reach our objectives. The results demonstrate that organizational support is the most important determinant of individual AO behaviours. Once controlled for, additional factors included three personal characteristics that increase propensity to demonstrate AO behaviour: education about AO, affirmation of Francophone identity, and competency in French. The sense of competency in English, on the other hand, has a negative association with AO of French-language service. A better understanding of these determinants enables us to refine our strategies to improve the awareness and education of future health and social service professionals on AO. Key Words: active offer behaviours, measurement, determinants, organizational support, individual behaviours, quantitative research.

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.

Conception d’outils de mesure de l’offre active de services sociaux et de santé en français en contexte minoritaire - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée; Drolet, Marie; Dubouloz Claire-Jehanne (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Dans les communautés francophones en situation minoritaire, le besoin d’une offre active des services en français, plutôt que d’un service qui suit la demande, est de plus en plus reconnu. Les professionnels en santé et en service social doivent être formés à cette approche et les résultats devront être évalués. Cet article décrit le processus de création et de validation de contenu (recension d’écrits, consultations d’experts, sondage Delphi pancanadien) de deux questionnaires portant sur les comportements caractéristiques de l’offre active de services sociaux et de santé en français : le premier mesurant les comportements individuels d’offre active des intervenants et le deuxième mesurant la perception de ces derniers du soutien organisationnel à l’offre active. Mots-clés : offre active, formation des professionnels de la santé et des services sociaux, évaluation, minorités, langue et services, soutien organisationnel

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

Handbook of Innovative Practices on the Integration of Social and Health Services in Official Languages in a Minority Context - Savard, Jacinthe; Savard, Sébastien; Van Kemenade, Solange; Josée, Benoît; Buhay, Corrina; Youbi, sara; Kubina, Lucy-Ann (2019)

Culture de sécurité des professionnels de santé en soins primaires : adapatation en langue française du questionnaire MOSPSC (« Medical Office Survey on Patient Safety Culture ») - Shih, C.; Buchet-Poyau, K.; Keriel-Gascou, M.; Quenon, J.-L.; Michel, P.; Touzet, S.; Chanalière, Marc (Revue d'Épidémiologie et de Santé Publique, 2022)
Contexte La culture de sécurité (CDS) rend compte de déterminants individuels et organisationnels. Son évaluation auprès des professionnels de santé en soins primaires (SP) peut être réalisée par des questionnaires auto-administrés, tel le « Medical Office Survey on Patient Safety Culture » (MOSPSC). Objectif Adapter en français le questionnaire MOSPSC et en étudier les propriétés psychométriques. Méthode Le questionnaire MOSPSC a fait l'objet d'une traduction avec analyse linguistique en langue française ; une rétrotraduction vers l'anglais a été réalisée, conformément aux recommandations de l'ISPOR. La version française du questionnaire a été diffusée à 415 professionnels de santé de 36 structures pluriprofessionnelles ambulatoires. L’étude des propriétés psychométriques (test-retest, α de Cronbach et analyse factorielle) a été conduite à partir des réponses des professionnels. Résultats Après analyse linguistique, la notion d’équipe a été traduite par celle de structure dans le questionnaire final. Le taux de participation des professionnels à l'enquête était de 64,1 % (266/415) ; 51,9 % (138/415) étaient des paramédicaux (principalement IDE ou kinésithérapeutes). Le coefficient α de Cronbach est de 0,94 pour l'ensemble des dimensions. Après analyse psychométrique, la dimension « signalement des évènements indésirables » a été ajoutée, et celle de « formation du personnel » intégrée à celle de « formation et standardisation des pratiques », portant à 13 le nombre de dimensions identifiées après analyse factorielle. Conclusion Le questionnaire MOSPSC adapté et validé en français peut être utilisé pour mesurer la CDS des professionnels en soins primaires en France. Son usage permettrait d'envisager à terme des comparaisons à l’échelle de chaque structure, pour y suivre l’évolution de la CDS, et dans le cadre de recherches nationales et internationales sur la gestion des risques en soins primaires.

Active Offer of French-Language Health Services for Francophone and Acadian Minority Communities in Canada - Joint position statement - Société Santé en français (2017)

L'offre active des services de santé en français dans les communautés francophones et acadienne en situation minoritaire au Canada - Énoncé de position commune - Société Santé en français (2017)

Delivery of Health Care Services in Both Official Languages: Let's see to it! - Société Santé et mieux-être du Nouveau- Brunswick (2009)

L’offre de services dans les deux langues officielles dans le domaine de la santé : à nous d’y voir ! - Société Santé et Mieux-être en français du Nouveau-Brunswick; Réseau-action formation et recherche (2009)

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif

La thérapie informatisée : une option pouvant faciliter l'accès à la thérapie chez les jeunes adultes ? - Talbot, France; LeBlanc, Josée; Jbilou, Jalila (Santé mentale au Quebec, 2015)
Introduction Les jeunes adultes ont, au Canada, les plus hauts taux de prévalence de l’anxiété et de la dépression, et sont aussi ceux qui utilisent le moins les services traditionnels de santé mentale. Faciliter l’accès à la thérapie chez les jeunes est ainsi particulièrement important, et ce, encore davantage dans les régions canadiennes plus rurales et auprès des minorités linguistiques. La thérapie informatisée pourrait être une option. Objectifs Cette étude vise à évaluer jusqu’à quel point l’autostigmatisation, un besoin d’autonomie et les attitudes face à la thérapie informatisée permettent de prédire l’intention d’utiliser cette thérapie chez de jeunes adultes francophones. L’impact de la visite du site Web d’une clinique virtuelle sur cette intention a également été évalué. Méthode Quarante-quatre étudiants fréquentant une université francophone du Nouveau-Brunswick ont complété, en ligne, des mesures autorapportées avant et suite à la visite du site Web de la clinique virtuelle MindSpot, en Australie, qui offre des thérapies informatisées. Résultats Une séquence de corrélations significatives entre les variables étudiées est observée, mais seules des attitudes plus positives à l’égard de la thérapie informatisée sont directement corrélées à une plus grande intention de l’utiliser. La visite du site Web a produit une augmentation significative et importante de l’intention d’utiliser la thérapie informatisée. Conclusions La thérapie informatisée pourrait faciliter l’accès aux traitements fondés sur les données probantes du stress, de l’anxiété et de la dépression chez les jeunes adultes francophones du Nouveau-Brunswick, voir d’autres parties du Canada. Cette approche demeure peu répandue encore à travers le pays. Mots-clés : thérapie autogérée, thérapie informatisée, jeunes adultes, anxiété, dépression, attitudes

Recruiting service providers with French proficiency: Tips and strategies - The Knowledge Institute on Child and Youth Mental Health and Addictions (2023)
This report is designed as a resource to support the "Kids Come First Health Team" in developing a strategy for recruiting, retaining and training human resources in Ontario’s Champlain health region. The report has been prepared by the Knowledge Institute on Child and Youth Mental Health and Addictions (the Knowledge Institute). The Knowledge Institute builds connections, shares knowledge and draws on expertise to enhance the skills of direct service providers and agencies across Ontario in order to strengthen Ontario’s mental health programs and services for all children, young people, families and caregivers. We wanted to discover what organizations are doing — particularly organizations in the health sector — to recruit service providers with French proficiency. We also wanted to learn about evidence-based practices for recruitment from the literature. The strategies and guiding principles provided in this resource were derived from an environmental scan that included a rapid, nonsystematic literature review. As well, we consulted with key stakeholders and leaders in the field who have direct experience with recruiting service providers with French proficiency.

Improving access to health services in French: The power of networking and knowledge mobilization, a proven Canadian Model - Tremblay, Michel; Leis, Anne (Linguistic Minorities and Society, 2021)
Language barriers have a detrimental impact on access to health services and compromise patients’ safety. The purpose of this article is to describe and evaluate how the Société Santé en français (SSF) and the 16 French Language Health (FLH) networks used networking and knowledge mobilization for improving access to health services in French for Francophone and Acadian minority communities (FAMC). Method: Data was extracted from the 2013-2018 program’s reports and evaluation. Results confirmed that networking effectively mobilized key partners for better access to health services in French regardless of location. This access increased incrementally as a function of the customized level of support provided to the system by the SSF and the FLH networks and, to a lesser extent, when FAMC represented over 3.5% of the total population in the region, province or territory. Networking and knowledge mobilization contribute to augmenting access to safe, quality health services in French for FAMC. Keywords: access, partnership and networking, active offer, language barriers, knowledge mobilization

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2025)
Ayant remarqué que certains gestionnaires démontraient une volonté d’améliorer les services en français au sein de leur organisation sans savoir comment s’y prendre, la Société Santé en français (SSF) et les réseaux de santé en français ont développé la plateforme en ligne accès éQUITÉ, dans le but d’accompagner les organisations dans la mise en place durable des services de santé en français. La Plateforme accès éQUITÉ regroupe des outils validés et fondés sur des données probantes qui aident les organisations à comprendre la marche à suivre pour mettre en place des pratiques exemplaires. Il s’agit d’une ressource conviviale comprenant divers modules de formations qui permettent aux gestionnaires d’évaluer les capacités de leur organisation à fournir des services de santé en français et d’améliorer leur prestation en suivant, à leur rythme, la démarche proposée. De plus, cette démarche est accompagnée d’un soutien personnalisé offert par des experts. Les ressources d’accès éQUITÉ aident les organisations à se préparer lorsqu'elles souhaitent présenter une demande au programme de reconnaissance des langues officielles (PRLO) d’Agrément Canada (fondée sur la norme "Accès aux services de santé et aux services sociaux dans les langues officielles"). De plus, à titre individuelle, toute personne membre certifié du Collège canadien des leaders en santé (CCLS) qui complète les formations disponibles dans accès éQUITÉ peut recevoir des crédits à l’égard des exigences de certification de cet organisme.

Pratiques novatrices en santé mentale pour les communautés francophones en situation minoritaire à Terre-Neuve-et-Labrador (T.-N.-L.) et dans les Territoires du Nord-Ouest (T.N.-O.) - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Création d'une grille d'observation pour simulations sur l'offre active de services de santé en français - Vincent, Coralie; Bodnaruc, Alexandra Maria; Kengneson, Cris-Carelle; Savard, Jacinthe; Giroux, Isabelle (Reflets, 2021)
Au Canada, il fut démontré que les communautés francophones vivant en situation linguistique minoritaire éprouvent des difficultés à se prévaloir de services sociaux et de santé dans leur langue de préférence, ce qui peut négativement affecter la qualité et la sécurité des services. L’offre active est une pratique visant à contrer les effets de la minorisation linguistique en invitant, de manière proactive et dès le premier contact, les bénéficiaires à s’exprimer dans la langue officielle de leur choix. Il n’existe actuellement aucun outil validé permettant l’évaluation de cette compétence auprès des futurs professionnels des domaines de la santé et des services sociaux. Cet article présente les étapes de création et de validation de Grille d’observation des indicateurs de compétence la en offre active de services en français, laquelle vise à soutenir les programmes de formation dans l’enseignement et l’évaluation de cette compétence au moyen de simulations. Mots-clés : minorités linguistiques, offre active de services en français, langue et services, qualité des soins, formation professionnelle en santé et service social, grille d’observation, validation

Évaluation de la fidélité interjuges d’une grille d’observation des comportements d’offre active de services en français dans le cadre d’activités d’apprentissage par simulation - Vincent, Coralie; Bodnaruc, Alexandra Maria; Savard, Jacinthe; Kengneson, Cris-Carelle; Benoît, Josée; Giroux, Isabelle (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
Résumé Dans les régions canadiennes où les communautés francophones vivent en situation minoritaire, l’offre active (OA) de services en français consiste à proposer des services en français de façon proactive et dès le premier contact. Dans le contexte des services sociaux et de santé, l’OA contribue à la qualité, à la sécurité et à l’équité des soins destinés à ces communautés. La Grille d’observation des indicateurs de compétence en OA a été créée pour évaluer cette compétence chez les futurs professionnels dans un contexte d’apprentissage par simulation. Le présent projet de recherche visait à poursuivre l’évaluation métrologique de la grille en mesurant sa fidélité interjuges grâce au coefficient de corrélation intraclasse (CCI). Les résultats ont démontré un niveau de fidélité globale élevé (CCI = 0,87), ce qui permet d’encourager l’utilisation de la grille dans les milieux d’apprentissage. Des recherches supplémentaires permettront d’évaluer la fidélité de la grille dans divers contextes et d’assurer l’amélioration continue de la formation des futurs professionnels sur l’OA. Mots-clés : outils d’évaluation, offre active de services en français, formation des professionnels de la santé, apprentissage par simulation, fidélité interjuges Abstract In Canadian Francophone minority communities, the active offer (AO) of French language services involves proactively offering services in French from the first point of contact. In the context of health and social services, the AO contributes to the quality, safety and equity of care within these communities. The AO Competency Indicator Observation Grid was created to assess AO competency among future professionals in a simulated learning environment. The purpose of this research project was to continue the metrological evaluation of the grid by measuring its inter-rater reliability using the intraclass correlation coefficient (ICC). The results demonstrated a high level of global reliability (ICC = 0.87), thus supporting the use of the grid in learning environments. Further research will evaluate the reliability of the grid in a variety of settings and ensure continued improvement in the training of future professionals on the AO. Keywords: assessment tools, active offer of French language services, health professional education, simulated learning, inter-rater reliability

Bottin des ressources en petite enfance à Iqaluit, Nunavut - youth primary health care (2020)
Ce bottin vise à aider les parents de jeunes enfants et les intervenants à avoir accès rapidement aux ressources pertinentes à la petite enfance qui sont disponibles à Iqaluit. Ce bottin présente une recension exhaustive de ces ressources en spécifiant le niveau d’accès aux services en français. Par ressources, on entend ici les services, les programmes, les ressources éducatives et autres sources d’information pertinente pour les périodes pré et péri natales, ainsi que pour les familles avec enfants de 0 à 6 ans.

Validation d’un questionnaire sur l’alphabétisme en santé des francophones en situation linguistique minoritaire - Zanchetta, Margareth; Maheu, Christine; Racine, Louise; Kaszap, Margot; Jbilou, Jalila; Giguère, Samuel; Reece, Daidre-Ann; Thélusma-Rémy, Marlene; Montgomery, Catherine; Xenocostas, Spyridoula; Parada, Henry; Talbot, Yves; et al. (Santé Publique, 2018)